Deoxygenative coupling of nitroarenes for the synthesis of aromatic azo compounds with CO using supported gold catalysts. Issue 56 (16th June 2015) - Li, Hai-Qian; Liu, Xiang; Zhang, Qi; Li, Shu-Shuang; Liu, Yong-Mei; He, He-Yong; Cao, Yong
Abstract : A simple ligand- and additive-free gold catalyst system that enables the CO-mediated reductive coupling of nitroarenes has been identified. Abstract : A facile and efficient catalytic system based on a mesostructured ceria-supported gold (Au/ meso -CeO2 ) catalyst was developed for the synthesis of various aromatic azo compounds by the reductive coupling of the corresponding nitroaromatics, using CO as the sole deoxygenative reagent, under additive-free and mild reaction conditions.